Brave face : a memoir - Hutchinson, Shaun David (Simon Pulse, an imprint of Simon & Schuster Children's Publishing Division, 2019)
At nineteen, Hutchinson was struggling to find the vocabulary to understand and accept who he was and how he fit into a community in which he couldn't see himself. Convinced that he couldn't keep going, that he had no future, Hutchinson followed through on trying to make that a reality -- an attempted suicide. Over time, he came to embrace life, and to find self-acceptance. In his deeply honest memoir, he takes readers through the journey of what brought him to the edge, and what has helped him truly believe that it does get better. -- adapted from jacket